Sosialisasi Spirit Perdamaian: Potensi Kampanye Pesan Toleransi dalam Film - Iqbal Azhari, Muhammad (Journal of Religion and Film, 2023)
This research aims to explore and analyze the potential of a tolerance message campaign through the medium of film as a tool to disseminate the spirit of peace. Involves analysis of films that carry the theme of tolerance and the messages conveyed to stimulate critical thinking and imbibe the values of tolerance in society. This research method includes literature study, using existing literature to collect data comprehensively. The research results show that films have great potential to be agents of social change by facilitating a deeper understanding of diversity and encouraging inclusive attitudes towards differences. Films not only function as entertainment, but also as an effective instrument in shaping people's views on tolerance issues. This in-depth analysis contributes to the literature on social media and tolerance, revealing that tolerance message campaigns in films are not only relevant, but also crucial in facing complex challenges in the contemporary era.